Visit frequency of Euglossine bees (Hymenoptera: Apidae) to mature fruits of Vanilla planifolia (Orchidaceae) - Lozano Rodríguez, Miguel Ángel; Luna Rodríguez, Mauricio; Pech Canché , Juan Manuel; Menchaca García , Rebeca Alicia; Cerdán Cabrera, Carlos Roberto (Instituto de Ecología, A.C., 2022)
Background and Aims: Visitation and fragrance collection in fruits of the genus Vanilla by Euglossine bees (Eulaema spp.) have previously been documented. However, in Vanilla planifolia, the most commonly cultivated species, this behavior has not yet been recorded. Thus, the objective of this study was to identify Euglossine visitors of the mature fruits of V. planifolia and to identify the frequency of these visitations. Methods: We held 11 observations set within a month (from March 6 to April 6, 2021) in an experimental Vanilla planifolia plantation with mature fruits of vanilla in Veracruz, Mexico. Each observation lasted for ten hours (from 8:00 to 18:00), representing a total of 110 hours sampling effort. During our observations we collected individuals of Euglossine bees directly from the mature fruits of vanilla to identify them at species level. We also recorded the frequency of Euglossini visits to mature fruits of V. planifolia. Key results: We identified five species belonging to three Euglossini genera visiting mature fruits of V. planifolia: Euglossa hemichlora, E. variabilis, Eulaema cingulata, E. polychroma, and Exaerete frontalis. The genus Eulaema had 72% of visits to V. planifolia fruits. Visitation frequency was dominated by Eulaema polychroma with 54% of total recorded visits (n=211). Conclusions: For the first time, Euglossine bees have been registered collecting scents in mature fruits of V. planifolia. Eulaema polychroma was the species with the highest percentage of visits to mature fruits V. planifolia to collect fragrances.